Carbohydrate Considerations for Athletes with a Spinal Cord Injury - Ruettimann, Belinda (Nutrients, 2021)
The Paralympic movement is growing in popularity, resulting in increased numbers of athletes with a spinal cord injury (SCI) competing in various sport disciplines. Athletes with an SCI require specialized recommendations to promote health and to maximize performance, as evidenced by their metabolic and physiological adaptations. Nutrition is a key factor for optimal performance; however, scientifically supported nutritional recommendations are limited. This review summarizes the current knowledge regarding the importance of carbohydrates (CHO) for health and performance in athletes with an SCI. Factors possibly affecting CHO needs, such as muscle atrophy, reduced energy expenditure, and secondary complications are analyzed comprehensively. Furthermore, a model calculation for CHO requirements during an endurance event is provided. Along with assessing the effectiveness of CHO supplementation in the athletic population with SCI, the evaluation of their CHO intake from the available research supplies background to current practices. Finally, future directions are identified. In conclusion, the direct transfer of CHO guidelines from able-bodied (AB) athletes to athletes with an SCI does not seem to be reasonable. Based on the critical role of CHOs in exercise performance, establishing recommendations for athletes with an SCI should be the overall objective for prospective research.